Adoption of a Population Health Approach in Sexual Health Programs and Services within Public Health in Ontario: A Multi-phase Mixed Methods Study - Frost, Linda (My University, 2021)
Since 2018, the Provincial Government of Ontario has begun transformation within the public health sector, which emphasizes the increased application of a population health approach. The goal of this transformation is to maximize the contribution of public health in improving the health of Ontarians by moving from a reactive to a proactive model that is focused on prevention. To support this transformation the standards that guide the programs and services provided through public health units underwent modernization in 2018. The emphasis of the modernized standards is about expanding the scope and reach of public health, by supporting the role of population health in the development and delivery of programs and services. This thesis used quantitative data to examine the extent that a population health approach was implemented in sexual health programs and services in public health units across Ontario. Qualitative data was gathered to explore public health managers’ and supervisors’ perceptions of barriers and facilitators that influenced the implementation of this approach. A mixed-methods study was used to determine if the qualitative findings helped our understanding of the quantitative results. This multi-phase mixed methods study involved four sequential phases. Phase 1 and 2 involved instrument development which included a literature review, input from experts, and testing; in phase 3 instrument administration was conducted; and phase 4 involved interviews with sexual health managers and supervisors. A qualitative descriptive approach was used as part of phases 1, 2, and in phase 4 for data collection and analysis using focus groups and semi-structured interviews with sexual health managers and supervisors delivering sexual health programs and services. The instrument was developed based on Health Canada’s Population Health Key Elements Template with multiple activities listed under each element and was administered in phase 3. Descriptive statistics were used to analyze this data. The Consolidated Framework for Implementation Research (CFIR) guided the development of the interviews for phase 4 and the qualitative analysis. Quantitative data showed that some population health elements were implemented more than others. For example, Address Determinants of Health and their Interactions was implemented by most health units while Employ Mechanisms for Public Involvement was implemented by a few. Qualitative data revealed that most factors influencing the implementation of a population health approach fit within CFIR’s domains of the inner and outer setting. For example Address Determinants of Health and Their Interactions and Focus on the Health of Populations were highly implemented by health units, due to factors such as organizational culture, and access to data. On the other hand, the elements Collaborate Across Sectors and Levels and Employ Mechanism for Public Involvement were less often implemented which were influenced by resources (e.g., human and financial) that were available to the health unit. This study fills an existing gap in the research and offers evidence of how to implement a population health approach within sexual health programs and services in public health.
Keywords: Public Health; Sexual Health; Population Health; Mixed-Methods